Acylhydrazone as a novel "Off–On–Off" fluorescence probe for the sequential detection of Al3+ and F−. (15th August 2018) - Wu, Yi-Peng; Rahman, Faiz-Ur; Bhatti, Muhammad Zeeshan; Yu, Shang-Bo; Yang, Bo; Wang, Hui; Li, Zhan-Ting; Zhang, Dan-Wei
Abstract : An acylhydrazone, SPBH, acts as a sequential fluorescence "Off–On–Off" probe for Al 3+ /F −, and the phenomenon was detectable by the naked eye. Abstract : A new acylhydrazone fluorescence probe, SPBH, was synthesized from salicylaldehyde and 4-(pyridin-4-yl)benzohydrazide (PBH ).SPBH exhibited high selectivity and a sensitive fluorescence response towards Al 3+, even in the presence of other competing metal ions in DMF/H2 O (1 : 1, v/v) medium. And, the chemosensor can even detect Al 3+ in the intracellular region of human non-small cell lung cancer H460 cells. The binding phenomenon ofSPBH was investigated by 1 H NMR spectroscopy and HR-MS. Mass spectrometry analysis showed a 1 : 1 complex formation ofSPBH with Al 3+ . The Job plot also confirmed its 1 : 1 interaction. ThisSPBH /Al 3+ complex exhibited excellent fluorescence "turn-off" properties towards the F − anion. Thus, SPBH acts as a sequential fluorescence "Off–On–Off" probe. The limits of detection for Al 3+ and F − were calculated from the titration curve and found to be 1.1 × 10 −7 M and 1.47 × 10 −6 M, respectively.